Prognostic role of neutrophil to lymphocyte ratio and platelet to lymphocyte ratio in prostate cancer: A meta-analysis of results from multivariate analysis. (December 2018) - Guo, Jinan; Fang, Jiequn; Huang, Xiangjiang; Liu, Yanfeng; Yuan, Yeqing; Zhang, Xueqi; Zou, Chang; Xiao, Kefeng; Wang, Jianhong
Abstract: Background: The prognostic role of neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) in patients with prostate cancer (PCa) remains inconsistent. Here we quantify the prognostic impact of these biomarkers and assess their consistency in PCa. Materials and methods: We systematically searched PubMed, Web of Science, and Embase for eligible studies embracing multivariate results. The Newcastle-Ottawa Scale were used to assess the study quality. Pooled hazard ratios (HRs), and 95% confidence intervals (CIs) were calculated. Results: A total of 7228 patients from 18 studies were included in the meta-analysis. Overall, elevated pretreatment NLR was associated with poor overall survival (OS, HR 1.58, 95% CI 1.41–1.78, P < 0.001), progression-free survival (PFS, HR 1.95, 95% CI 1.53–2.49, P < 0.001) and biochemical recurrence-free survival (BRFS, HR 1.37, 95% CI 1.07–1.75, P = 0.011). And high pretreatment PLR was correlated with more inferior PFS (HR 1.62, 95% CI 1.20–2.19, P = 0.002), OS (HR 1.70, 95% CI 1.34–2.15, P < 0.001) and cancer-specific survival (CSS, HR 2.02, 95% CI 1.24–3.29, P = 0.005). Moreover, the subgroup analyses did not alter the direction of results for OS and PFS. Conclusion : Based on these findings, elevated NLR and PLR was associated with poor oncologic outcomes, and they can serve as prognostic factors in PCa patients.